Sum of Sine Squares

Geometry Level 2

sin 2 1 8 + sin 2 3 0 . \sin^2 18^ \circ + \sin ^2 30 ^ \circ.

Which of the following is equal to the above expression?

sin 2 3 6 \sin^2 36 ^ \circ sin 2 4 2 \sin^2 42 ^ \circ sin 2 4 8 \sin^2 48 ^ \circ sin 2 5 4 \sin^2 54 ^ \circ

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

6 solutions

Chew-Seong Cheong
Jun 18, 2015

X = sin 2 1 8 + sin 2 3 0 = 1 2 ( 1 cos 3 6 ) + 1 4 = 3 4 1 2 cos 3 6 = 1 2 + 1 2 ˙ 1 2 1 2 cos 3 6 = 1 2 + 1 2 ( cos 3 6 + cos 10 8 cos 3 6 ) [See Note] = 1 2 + 1 2 cos 10 8 = 1 2 + 1 2 ( 2 cos 2 5 4 1 ) = cos 2 5 4 = sin 2 3 6 \begin{aligned} X & = \sin^2{18^\circ} + \sin^2 {30^\circ} \\ & = \frac {1}{2} (1 - \cos{36^\circ} )+ \frac{1}{4} \\ & = \frac{3}{4} -\frac{1}{2} \cos{36^\circ} \\ & = \frac{1}{2} + \frac{1}{2}\dot{}\color{#3D99F6}{\frac{1}{2}} - \frac{1}{2} \cos{36^\circ} \\ & = \frac{1}{2} + \frac{1}{2} \left(\color{#3D99F6}{\cos{36^\circ} + \cos{108^\circ}} - \cos{36 ^ \circ}\right) \quad \color{#3D99F6}{\text{[See Note]}} \\ & = \frac{1}{2} + \frac{1}{2} \cos{108^\circ} \\ & = \frac{1}{2} + \frac{1}{2}(2\cos^2{54^\circ}-1) \\ & = \cos^2{54^\circ} \\ & = \boxed{\sin^2{36^\circ}} \end{aligned}


Note: \color{#3D99F6}{\text{Note:}}

cos 3 6 + cos 10 8 = cos 3 6 + cos ( 3 ( 3 6 ) ) = cos 3 6 + 4 cos 3 3 6 3 cos 3 6 = 2 cos 3 6 ( 2 cos 2 3 6 1 ) = 2 cos 3 6 cos 7 2 = 2 cos 3 6 sin 1 8 = 2 cos 3 6 sin 1 8 cos 1 8 cos 1 8 = cos 3 6 sin 3 6 cos 1 8 = sin 7 2 2 cos 1 8 = cos 1 8 2 cos 1 8 = 1 2 \begin{aligned} \cos 36^\circ + \cos 108^\circ & = \cos 36^\circ + \cos (3(36^\circ)) \\ & = \cos 36^\circ + 4\cos^3 36^\circ - 3 \cos 36^\circ \\ & = 2 \cos 36^\circ (2\cos^2 36^\circ - 1) \\ & = 2 \cos 36^\circ \cos 72^\circ \\ & = 2 \cos 36^\circ \sin 18^\circ \\ & = \frac{2 \cos 36^\circ \sin 18^\circ \cos 18^\circ}{\cos 18^\circ} \\ & = \frac{\cos 36^\circ \sin 36^\circ}{\cos 18^\circ} \\ & = \frac{\sin 72^\circ}{2 \cos 18^\circ} \\ & = \frac{\cos 18^\circ}{2 \cos 18^\circ} \\ & = \boxed{\frac{1}{2}} \end{aligned}

Moderator note:

You should explain why cos 3 6 + cos 10 8 = 1 2 \cos 36 ^ \circ + \cos 108^ \circ = \frac{1}{2} . That is not obvious.

(Fixed) Typo in the 4th line, should be a - instead of + cos 3 6 + \cos 36 ^ \circ .

In the ancient days, this was known as:

In a unit circle, the sum of areas of the squares constructed on an inscribed regular decagon and hexagon, are equal to that on a pentagon.

Calvin Lin Staff - 5 years, 12 months ago

Log in to reply

how to prove that?

de azalea - 5 years, 11 months ago

Log in to reply

I've added a solution that avoids trigonometry. It uses 3-D geometric visualization.

Calvin Lin Staff - 5 years, 11 months ago

this is really nice sir!

Gaurav Jain - 5 years, 11 months ago

My bad! How 'cos108 degree' comes on 5th line ? Can you explain it for me, please ?

Asheq Elahi - 5 years, 12 months ago

Log in to reply

I have changed the note to explain it.

Chew-Seong Cheong - 5 years, 1 month ago

  1. satır cos108 ?

Soner Karaca - 5 years, 12 months ago

Log in to reply

I have changed the note to explain it.

Chew-Seong Cheong - 5 years, 1 month ago

cos36+cos108=1/2.....? and cos72+cos144=- 1/2 ?

Soner Karaca - 5 years, 11 months ago

Log in to reply

I have changed the note to explain it.

Chew-Seong Cheong - 5 years, 1 month ago

i did not understand from line 4.

om sai - 5 years, 11 months ago

Log in to reply

I have changed the note to explain it.

Chew-Seong Cheong - 5 years, 1 month ago

It's been a really long time since I've done this, but thank you for the notes. This really helps. I guess I need a hell of a lot more practice.

Conrad Fairchild - 4 years, 9 months ago
Fidel R.
Jun 22, 2015

So instead of using identities, I resorted to using actual values and miraculously arrived to a solution. The reason I selected this approach was because 30º is a special angle and its sine can be easily computed; it's one half (simply draw an equilateral triangle, bisect one of the angles, and use the pythagorean theorem to determine the ratio of the sides). Therefore, I was able to collapse the problem a little bit.

sin 2 ( 18 ) + sin 2 ( 30 ) = sin 2 ( θ ) \sin^{2} (18) + \sin^{2} (30) = \sin^{2} (\theta) sin 2 ( 18 ) + ( 1 2 ) 2 = sin 2 ( θ ) \sin^{2} (18) + (\frac{1}{2})^{2} = \sin^{2} (\theta) sin 2 ( 18 ) + 1 4 = sin 2 ( θ ) \sin^{2} (18) + \frac{1}{4} = \sin^{2} (\theta)

Now, the sine of 18º is not as easily computable as that of 30º, but it can still be done. Take the following 72, 72, 36 triangle:

The non-vertical dotted line bisects the 72º angle on the left, thus creating a smaller 72, 72, 36 triangle at the bottom of the big triangle. I arbitrarily gave a length of 1 to the line that both triangles share. That line is opposite to one of the 72º of the small triangle; therefore, the line that is opposite to the other 72º angle of the small triangle should also have a length of 1; that happens to be the non-vertical dotted line. There is a third triangle: a 36, 36, 108 triangle that rests on top of the smaller 72, 72, 36 triangle. The non-vertical dotted line is opposite to one of the 36º angles of this new triangle; therefore, the line that is opposite to the other 36º angle of the new triangle should have the same length as the non-vertical dotted line, which happens to be 1. As a result the distance from the top of the big triangle to the point where the rightmost line of the big triangle and the non-vertical dotted line intersect is 1. The remaining portion of the rightmost line of the big triangle I simply labeled "X".

The two triangles that have 72º, 72º and 36º as their angles are similar. Therefore, we can write a simple ratio relating the lengths of the sides.

o p p o s i t e 72 b i g o p p o s i t e 36 b i g = o p p o s i t e 72 s m a l l o p p o s i t e 36 s m a l l \frac{opposite 72 big}{opposite 36 big} = \frac{opposite 72 small}{opposite 36 small} 1 + X 1 = 1 X \frac{1+X}{1} = \frac{1}{X}

Cross multiply and simplify:

( 1 + X ) ( X ) = ( 1 ) ( 1 ) (1+X)(X) = (1)(1) X + X 2 = 1 X + X^{2} = 1 X 2 + X 1 = 0 X^{2} + X - 1 = 0

To solve for "X", use the quadratic formula. Keep in mind that "X" is a distance; therefore, only the positive value matters.

X = 1 + 1 2 4 ( 1 ) ( 1 ) 2 ( 1 ) X = \frac{-1 + \sqrt{1^{2} - 4(1)(-1)}}{2(1)} X = 1 + 1 + 4 2 X = \frac{-1 + \sqrt{1 + 4}}{2} X = 1 + 5 2 X = \frac{-1 + \sqrt{5}}{2}

Now, to calculate the sine of 18, bisect the 36º angle of the big triangle. Because the big triangle is isosceles, the line that bisects the 36º angle also bisects the line with length 1 at the bottom. This new 18, 72, 90 triangle thus has a side of length 0.5 that is opposite the 18º angle and a hypotenuse of "1 + X". Because we now know the value of "X", we can compute the sine of 18.

sin θ = o p p o s i t e h y p o t e n u s e \sin \theta = \frac{opposite}{hypotenuse} sin ( 18 ) = 1 2 1 + X \sin (18) = \frac{ \frac{1}{2} }{1+X} sin ( 18 ) = 1 2 1 + 1 + 5 2 \sin (18) = \frac{ \frac{1}{2} }{1+ \frac{-1 + \sqrt{5}}{2} } sin ( 18 ) = 1 2 2 2 + 1 + 5 2 \sin (18) = \frac{ \frac{1}{2} }{ \frac{2}{2}+ \frac{-1 + \sqrt{5}}{2} } sin ( 18 ) = 1 2 2 1 + 5 2 \sin (18) = \frac{ \frac{1}{2} }{ \frac{2 -1 + \sqrt{5}}{2} } sin ( 18 ) = 1 2 1 + 5 2 \sin (18) = \frac{ \frac{1}{2} }{ \frac{1 + \sqrt{5}}{2} } sin ( 18 ) = 1 1 + 5 \sin (18) = \frac{1}{1 + \sqrt{5}} sin ( 18 ) = 1 1 + 5 × 1 5 1 5 \sin (18) = {\frac{1}{1 + \sqrt{5}}} \times {\frac{1 - \sqrt{5}}{1 - \sqrt{5}}} sin ( 18 ) = 1 5 1 5 \sin (18) = \frac{1 - \sqrt{5}}{ 1 - 5} sin ( 18 ) = 1 5 4 \sin (18) = \frac{1 - \sqrt{5}}{ -4 } sin ( 18 ) = 5 1 4 \boxed{ \sin (18) = \frac{\sqrt{5}-1}{ 4}}

Now, back to the problem.

sin 2 ( 18 ) + 1 4 = sin 2 ( θ ) \sin^{2} (18) + \frac{1}{4} = \sin^{2} (\theta) ( 5 1 4 ) 2 + 1 4 = sin 2 ( θ ) (\frac{\sqrt{5}-1}{ 4})^{2} + \frac{1}{4} = \sin^{2} (\theta) ( 5 1 ) 2 16 + 1 4 = sin 2 ( θ ) \frac{(\sqrt{5}-1)^{2}}{ 16} + \frac{1}{4} = \sin^{2} (\theta) 5 2 5 + 1 16 + 4 16 = sin 2 ( θ ) \frac{5 - 2\sqrt{5} + 1}{ 16} + \frac{4}{16} = \sin^{2} (\theta) 6 2 5 16 + 4 16 = sin 2 ( θ ) \frac{6 - 2\sqrt{5}}{ 16} + \frac{4}{16} = \sin^{2} (\theta) 10 2 5 16 = sin 2 ( θ ) \frac{10 - 2\sqrt{5}}{ 16} = \sin^{2} (\theta) 5 5 8 = sin 2 ( θ ) \frac{5 - \sqrt{5}}{8} = \sin^{2} (\theta) sin ( θ ) = 5 5 8 \sin (\theta) = \frac{\sqrt{5 - \sqrt{5}}}{\sqrt{8}}

We will now introduce the variable "U"

U = 2 θ U = 2\theta θ = U 2 \theta = \frac{U}{2} sin ( U 2 ) = 5 5 8 \sin (\frac{U}{2}) = \frac{\sqrt{5 - \sqrt{5}}}{\sqrt{8}}

Now, use the half angle identity. I am only concerned with the positive value because all of the angles are in the first quadrant.

1 cos ( U ) 2 = 5 5 8 \sqrt{\frac{1 - \cos (U)}{2}} = \frac{\sqrt{5 - \sqrt{5}}}{\sqrt{8}} 1 cos ( U ) 2 = 5 5 8 \frac{1 - \cos (U)}{2} = \frac{5 - \sqrt{5}}{8} 8 ( 1 cos ( U ) ) = 2 ( 5 5 ) 8(1 - \cos (U)) = 2(5 - \sqrt{5}) 4 ( 1 cos ( U ) ) = 5 5 4(1 - \cos (U)) = 5 - \sqrt{5} 4 4 cos ( U ) = 5 5 4 - 4\cos (U) = 5 - \sqrt{5} 4 cos ( U ) = 1 5 - 4\cos (U) = 1 - \sqrt{5} cos ( U ) = 1 5 4 = 5 1 4 \cos (U) = \frac{1 - \sqrt{5}}{-4} = \frac{\sqrt{5} - 1}{4}

That number looks awfully familiar. As a matter of fact, we earlier determined that this number is the value for the sine of 18º (see the boxed value above).

cos ( U ) = sin ( 18 ) \cos (U) = \sin (18) sin ( 90 U ) = sin ( 18 ) \sin (90 - U) = \sin(18) 90 U = 18 90 - U = 18 U = 90 18 U = 90 - 18 U = 72 U = 72 2 θ = 72 2\theta = 72 θ = 36 \boxed{\theta = 36}

FYI, there is no need to start every equation on a new line.

Use \ ( Latex code \ ) (no spaces) for in line equations.

Calvin Lin Staff - 5 years, 11 months ago
Calvin Lin Staff
Jun 22, 2015

We will prove that sin 2 1 8 + sin 2 3 0 = sin 2 3 6 \sin^2 18 ^ \circ + \sin ^2 30 ^ \circ = \sin^2 36 ^ \circ .

Here is a "pure synthetic geometry" proof of this result. Consider an icosahedron inscribed in a sphere of radius 1. Let the top vertex by T T and the bottom vertex by B B .

The bases of the 5 triangles that meet at T T would form a regular pentagon. Let these vertices be T 1 , T 2 , T 3 , T 4 , T 5 T_1, T_2, T_3, T_4, T_5 , and let this plane be Π T \Pi _T .

The bases of the 5 triangles that meet at B B would form a regular pentagon. These 2 pentagons are rotated from each other. Let these vertices be B 1 , B 2 , B 3 , B 4 , B 5 B_1, B_2, B_3, B_4, B_5 , where B 1 B_1 is between T 1 T_1 and T 5 T_5 . Let this plane be Π S \Pi _S .

Consider the projection of T 1 T_1 down onto Π S \Pi _ S and call it P P . Then, by definition T 1 P B 1 T_1 P B_ 1 forms a right triangle at P P . We already have T 1 B 1 = 2 sin 3 6 T_1 B_1 = 2 \sin 36 ^\circ and P B 1 = 2 sin 1 8 P B_1 = 2 \sin 18 ^\circ from the above discussion. Thus, we just have to show that T 1 C = 2 sin 3 0 = 1 T_1 C = 2 \sin 30 ^\circ = 1 .

This is pretty obvious and is left as an exercise to the reader.

Hint: Let O O be the center of the sphere. How do the points T , O , S T, O, S relate to planes Π T , Π S \Pi_T, \Pi_S ?

How could it be a level 2 question? It should have been level 6 or something like that...

Istiak Reza - 5 years, 11 months ago

Log in to reply

I think the reason is that this problem can be solved very easily with a calculator. But I agree with you, if you don't use a calculator or Wolfram Alpha this is a problem of a higher level.

Arturo Presa - 5 years, 10 months ago

Log in to reply

Yes, those who simply used a calculation device may have obtained the answer, but they would not have understood how to solve similar problems properly.

Calvin Lin Staff - 5 years, 10 months ago

Log in to reply

@Calvin Lin I completely agree with you in that respect.

Arturo Presa - 5 years, 10 months ago

@Calvin Lin What would one have to do without a calculator or using guess and check on the answer choices? The solutions here all seemed to have worked backwards from already knowing the answer.

Ben Lou - 3 years, 3 months ago

Log in to reply

@Ben Lou If you treat it as "Prove this trigonometric identity", Chew's solution shows a possible approach where you work from both ends.

Alternatively, Fidel's solution of "Let's calculate these actual values and compare" also works.

If you are asking "How do I know that some random trigonometric expression will be equal to something that is very nice", then the honest answer is "Well, in most cases, it will not". E.g. I do not expect sin 2 1 + sin 2 1 2 \sin^2 1 ^ \circ + \sin ^2 12 ^ \circ to have a meaningful result. At a meta level, these problems are chosen to showcase an interesting fact, and so we know that there is a "nice" solution.

Calvin Lin Staff - 3 years, 3 months ago

Log in to reply

@Calvin Lin Agree with you that they will have a nice solution... however even knowing that it would be hard to find the answer without the answer choices or a calculator as there are too many answers that could be considered "nice".

Ben Lou - 3 years, 3 months ago

How will they use calculators? Even if they compute the value of the expression, the calculator won't give an exact form and they won't be able to deduce that it equals any of the options.

Anupam Nayak - 5 years, 6 months ago

Log in to reply

@Anupam Nayak There are calculators that give exact values as well as the website Wolfram Alpha. But I see that the members of Brilliant are finding ways of improving the format of the answers so that it is more difficult to solve them just using technology. This makes the questions more interesting and challenging

Arturo Presa - 5 years, 6 months ago

@Anupam Nayak Have a look at this link. I could do this on my calculator too. http://www.wolframalpha.com/input/?i=arcsin%E2%88%9A[%28sin+18%29^2+%2B+sin%2830%29^2%29]

Davy Ker - 5 years, 5 months ago
Arturo Presa
Jul 22, 2015

First we will prove that cos 7 2 = 5 1 4 \cos 72^\circ= \frac{\sqrt{5}-1}{4} . To do this we are going to use the fact that the complex fifth roots of 1, which are different from 1, are w 1 , w 2 , w ˉ 1 , w_{1}, w_{2}, \bar{w}_{1}, and w ˉ 2 , \bar{w}_{2}, where w 1 = cos 7 2 + i sin 7 2 w_{1}= \cos 72^\circ+i\sin 72^\circ and w 2 = cos 14 4 + i sin 14 4 . w_{2}= \cos 144^\circ+i \sin 144^\circ. Then ( x w 1 ) ( x w ˉ 1 ) ( x w 2 ) ( x w ˉ 1 ) = (x-w_{1})(x-\bar{w}_{1})(x-w_{2})(x-\bar{w}_{1})= = x 5 1 x 1 = x 4 + x 3 + x 2 + x + 1. ( ) = \frac{x^{5}-1}{x-1}= x^{4}+x^{3}+x^{2}+x+1.\:\:\:\:(*) Since w 1 + w ˉ 1 = 2 cos 7 2 w_{1}+\bar{w}_{1} = 2\cos72^\circ , w 2 + w ˉ 2 = 2 cos 14 4 w_{2}+\bar{w}_{2} = 2\cos 144^\circ , w 1 w ˉ 1 = 1 w_{1}\bar{w}_{1} = 1 , and w 2 w ˉ 2 = 1 w_{2}\bar{w}_{2} = 1 then the equation (*) can be written like this ( x 2 2 cos 7 2 x + 1 ) ( x 2 2 cos 14 4 x + 1 ) = x 4 + x 3 + x 2 + x + 1. (x^{2}- 2\cos 72^\circ x+1)(x^{2}- 2\cos 144^\circ x+1)= x^{4}+x^{3}+x^{2}+x+1. Expanding the product in the left side of the equation and making corresponding coefficients equal, we obtain the following equations

cos 7 2 + cos 14 4 = 1 2 \cos 72^\circ + \cos 144^\circ =-\frac{1}{2} and cos 7 2 cos 14 4 = 1 4 . \cos 72^\circ \cos 144^\circ =-\frac{1}{4}.

Therefore cos 7 2 \cos 72^\circ , and cos 14 4 \cos 144^\circ will be the positive and the negative solutions, respectively, of the equation z 2 + 1 2 z 1 4 = 0. z^{2} + \frac{1}{2}z-\frac{1}{4}=0. Therefore cos 7 2 = 5 1 4 \cos 72^\circ =\frac{\sqrt{5}-1}{4} . Now what follows is a lot easier sin 2 1 8 + sin 2 3 0 = cos 2 7 2 + sin 2 3 0 = ( 5 1 4 ) 2 + ( 1 2 ) 2 = \sin^{2} 18^\circ+\sin^{2} 30^\circ =\cos^{2} 72^\circ+\sin^{2} 30^\circ=(\frac{\sqrt 5-1}{4})^{2}+(\frac{1}{2})^{2}= = 5 5 8 = 1 5 1 4 2 = 1 cos 7 2 2 = sin 2 3 6 =\frac{5-\sqrt 5}{8}= \frac{1-\frac{\sqrt 5 -1}{4}}{2}=\frac{1-\cos 72^\circ}{2}=\sin^{2} 36^\circ

and then the answer must be sin 2 3 6 . \sin^{2} 36^\circ.

Mas Mus
Jan 31, 2017

sin 2 1 8 + sin 2 3 0 = sin 2 1 8 + 1 4 = sin 2 1 8 + cos 1 8 4 cos 1 8 = sin 2 1 8 + cos 9 0 cos 1 8 4 cos 1 8 = sin 2 1 8 + 2 sin 5 4 sin 3 6 4 cos 1 8 = sin 2 1 8 + 4 sin 5 4 sin 1 8 cos 1 8 4 cos 1 8 = sin 1 8 ( sin 1 8 + sin 5 4 ) = 2 sin 1 8 sin 3 6 cos 1 8 = sin 2 3 6 \begin{aligned}\sin^{2}{18^\circ}+\sin^{2}{30^\circ}&=\sin^{2}{18^\circ}+\frac{1}{4}\\\\&=\sin^{2}{18^\circ}+\frac{-\cos{18^\circ}}{-4\cos{18^\circ}}\\\\&=\sin^{2}{18^\circ}+\frac{\cos{90^\circ}-\cos{18^\circ}}{-4\cos{18^\circ}}\\\\&=\sin^{2}{18^\circ}+\frac{-2\sin{54^\circ}\sin{36^\circ}}{-4\cos{18^\circ}}\\\\&=\sin^{2}{18^\circ}+\frac{-4\sin{54^\circ}\sin{18^\circ}\cos{18^\circ}}{-4\cos{18^\circ}}\\\\&=\sin{18^\circ}\left(\sin{18^\circ}+\sin{54^\circ}\right)\\\\&=2\sin{18^\circ}\sin{36^\circ}\cos{18^\circ}\\\\&=\color{#20A900}{\sin^{2}{36^\circ}}_\square\end{aligned}

Washeef Mohammad
Jan 7, 2016

Let θ = 1 8 \theta = 18^\circ 5 θ = 9 0 θ = 9 0 4 θ cos θ = sin 4 θ = 4 sin θ cos θ cos 2 θ \Leftrightarrow 5\theta=90^\circ \Leftrightarrow \theta=90^\circ -4\theta \Leftrightarrow \cos\theta=\sin4\theta=4\sin\theta\cos\theta\cos2\theta 4 sin θ cos 2 θ = 1 ; [ cos θ 1 ] \Leftrightarrow 4\sin\theta\cos2\theta=1; [\because \cos\theta \ne 1] 4 sin θ cos ( 5 θ 3 θ ) = 1 4 sin θ cos ( 9 0 3 θ ) = 1 \Leftrightarrow 4\sin\theta\cos(5\theta-3\theta)=1 \Leftrightarrow 4\sin\theta\cos(90^\circ-3\theta)=1

4 sin θ sin 3 θ = 1 \therefore 4\sin\theta\sin3\theta=1 ..........(i)

Now let

sin 2 α = sin 2 1 8 + sin 2 3 0 sin 2 α = sin 2 θ + 1 4 \sin^2\alpha=\sin^{2}18^\circ+\sin^{2}30^\circ \Leftrightarrow \sin^2\alpha=\sin^{2}\theta+\frac{1}{4}

2 sin 2 α = 2 sin 2 θ + 1 2 \Leftrightarrow 2\sin^2\alpha=2\sin^{2}\theta+\frac{1}{2}

1 cos 2 α = 1 cos 2 θ + 1 2 cos 2 θ cos 2 α = 1 2 \Leftrightarrow 1-\cos2\alpha=1-\cos2\theta+\frac{1}{2} \Leftrightarrow \cos2\theta-\cos2\alpha=\frac{1}{2}

2 sin ( 2 α + 2 θ 2 ) sin ( 2 α 2 θ 2 ) = 1 2 \Leftrightarrow 2\sin(\frac{2\alpha+2\theta}{2})\sin(\frac{2\alpha-2\theta}{2})=\frac{1}{2}

4 sin ( α + θ ) sin ( α θ ) = 1 \Leftrightarrow 4\sin(\alpha+\theta)\sin(\alpha-\theta)=1 ..........(ii)

no(i) \equiv no(ii) iff

α + θ = 3 θ \alpha+\theta=3\theta and α θ = θ \alpha-\theta=\theta α = 2 θ \iff \alpha=2\theta α = 2 × 1 8 = 3 6 \therefore \alpha=2\times 18^\circ=\boxed {36^\circ}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...